2007
DOI: 10.1099/mic.0.2007/008896-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressing antioxidant enzymes enhances naphthalene biodegradation in Pseudomonas sp. strain As1

Abstract: We tested the hypothesis that during metabolism of naphthalene and other substrates by Pseudomonas sp. strain As1 oxidative stress arises and can be reduced by antioxidant enzymes. Our approach was to prepare plasmid constructs that conferred expression of two single antioxidant enzymes [Fpr (ferredoxin-NADP + reductase) and SOD (superoxide dismutase)] and the pair of enzymes SOD plus AhpC (alkyl hydroperoxide reductase). The fpr, sodA and ahpC genes were placed under the transcriptional control of both the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
0
27
1
Order By: Relevance
“…Specific genes, such as those encoding chaperones, have been reported to relieve up to 85% of the growth decrease caused by the addition of n-butanol in Clostridium (46) and based on our results may prove to be a valuable approach in E. coli as well. Similar relief may be provided via expression of redox stress response enzymes such as SodA and YqhD, both of which have also been reported for use in relieving growth defects due to oxidative stresses (23,35).…”
Section: Resultsmentioning
confidence: 99%
“…Specific genes, such as those encoding chaperones, have been reported to relieve up to 85% of the growth decrease caused by the addition of n-butanol in Clostridium (46) and based on our results may prove to be a valuable approach in E. coli as well. Similar relief may be provided via expression of redox stress response enzymes such as SodA and YqhD, both of which have also been reported for use in relieving growth defects due to oxidative stresses (23,35).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the decrease in the quality of vegetables caused by DBP pollution has posed a potential risk for human health through the food chain. Previous studies have shown that many pollutants are redox-active (Kang et al 2007; Kreiner et al 2002). The redox products could attack the cell membrane bringing about oxidative stress to the body and even causing cell death or canceration (Zhang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the hexadecane degradation pathway is present in the A. oleivorans DR1 genome [38][41]. Many genes involved in hexadecane utilization, including alkane 1-monooxygenase encoded by alkB (AOLE_10550) and aldehyde dehydrogenase encoded by putA (AOLE_06655) were downregulated in the presence of the plasmid (Table 3).…”
Section: Resultsmentioning
confidence: 99%